2005
DOI: 10.4049/jimmunol.174.8.4621
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory NK Receptor Ly49Q Is Expressed on Subsets of Dendritic Cells in a Cellular Maturation- and Cytokine Stimulation-Dependent Manner

Abstract: Ly49Q is a member of the Ly49 family that is expressed on Gr-1+ cells but not on NK and NKT cells. Ly49Q appears to be involved in regulating cytoskeletal architectures through ITIM-mediated signaling. We provide evidence that dendritic cells (DCs) of certain maturational states expressed Ly49Q, and that IFN-α plays an important role in its regulation. Freshly prepared murine plasmacytoid pre-DCs as well as Flt3L-induced plasmacytoid pre-DCs expressed Ly49Q, whereas freshly prepared myeloid DCs did not. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Ly49Q is expressed on myeloid lineage cells, in particular plasmacytoid dendritic cells (4,31). Thus, cell types other than NK cells use receptor masking to adapt receptor accessibility and consequently receptor function to self-MHC-I.…”
Section: Ly49b and Ly49qmentioning
confidence: 99%
“…Ly49Q is expressed on myeloid lineage cells, in particular plasmacytoid dendritic cells (4,31). Thus, cell types other than NK cells use receptor masking to adapt receptor accessibility and consequently receptor function to self-MHC-I.…”
Section: Ly49b and Ly49qmentioning
confidence: 99%
“…Ly49Q is expressed neither on NK nor NKT cells, but on plasmacytoid dendritic cells (DCs), macrophages, and neutrophils. 7,9,10 The expression of Ly49Q appears to be regulated during the maturation of these cells and is significantly up-regulated by IFN-␥ treatment. 7,10,11 Ly49Q can associate with both Src homology 2-containing protein tyrosine phosphatase (SHP)-1 and SHP-2 in a tyrosine phosphorylation-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, murine Ly49Q has been reported to be expressed on cDCs and pDCs and has been suggested to regulate their functions (21,26). It has also been reported that human thymic pDCs regulate the nTreg developmental process (9,10).…”
Section: Figurementioning
confidence: 99%
“…On encountering MHC class I molecules, they transmit inhibitory signals to prevent NK cells from mediating cytotoxicity (17). At present, it is known that some members of the Ly49 family transmit activating, instead of inhibitory, signals and some are expressed on T cells and DCs and perform distinct functions (18)(19)(20)(21)(22). On the basis of the structural characteristics of Ly49s3-that is, the presence of a positively charged arginine residue in the transmembrane domain for association with adaptor proteins containing immunoreceptor tyrosinebased activating motifs-it has been predicted to be an activating receptor.…”
Section: Loss Of Ly49s3 Gene Expression In Hhr Thymic Cdcsmentioning
confidence: 99%